Kemampuan Pencarian Informasi Menggunakan Model Kuhlthau Information Seeking Mahasiswa PAI Angkatan 2022 Kelas B dan E - Novita, Seli (LIBTECH: LIBRARY AND INFORMATION SCIENCE JOURNAL, 2024)
This research examines the information seeking abilities of Islamic Religious Education (PAI) students class 2022 class B and E using the Kuhlthau Information Seeking Model. Kuhlthau's model focuses on six stages of information search which include initiation, selection, exploration, formulation,collection, and presentation. This research uses a qualitativedescriptive method with data collection techniques through observation, in-depth interviews and document analysis. The research results show that the majority of students experience difficulties at the exploration and formulation stages, where they feel confused and less confident in identifying and formulatingtopics that suit their information needs. At the initiation andselection stages, students tend to rely on easily accessible information sources such as the internet, but pay less attention to the validity and credibility of these sources. This research also identifies factors that influence information search abilities, including information literacy abilities, access to information sources, and support from lecturers. These findings indicate theneed to increase information literacy through a more integrated curriculum and ongoing training. Recommendations are provided to develop a comprehensive information literacy training program to help students improve their informationsearch skills according to expected academic standards. Thisresearch contributes to a deeper understanding of the dynamics of information seeking among PAI students and offers discourse for the development of more effective learning strategies in supporting critical and systematic information seeking processes.